Behaviour and design calculations of rectangular CFST beam-columns with slender sections. (1st November 2020) - Zarringol, Mohammadreza; Thai, Huu-Tai; Ngo, Tuan; Patel, Vipulkumar
Highlights: Finite element model for high-strength rectangular CFST beam-columns is presented. Accuracy of Australian, European and American design standards is examined. Australian and European standards overestimate strength of slender CFST beam-columns. Recommendations based on Australian and European design standards are proposed. Abstract: In this paper, design calculations of Concrete-Filled Steel Tubular (CFST) columns with slender sections subjected to combined axial compression and bending are considered based on the Australian code (AS 5100), American code (AISC 360–16) and European code (EC 4) approaches. A Finite Element (FE) model is developed to predict the strength of rectangular CFST slender section beam-columns. The experimental data is collected and used to examine the accuracy of AS 5100, AISC 360–16 and EC 4 in predicting the strengths of CFST slender section beam-columns, and to validate the FE model. In addition, based on the test results, FE analysis results and limits specified in the codes, design procedures are developed to propose modifications to the current AS 5100 and EC 4 to improve their accuracy in designing CFST slender section columns. The effects of material strengths on the accuracy of the proposed methods are also investigated. The results indicate that, while AISC 360–16 provides conservative strength predictions, the current AS 5100 and EC 4 overestimate the strengths of CFST slender section beam-columns. The comparative study also shows that better strength predictions are achieved using the proposed design procedures.